Taṭbīq Ta‘līm al-Naḥwu bi-Istikhdām Amṡilah al-Āyāt al-Qur’āniyyah li-al-Ṣaff al-Sābi‘ Taḥfīẓ al-Qur’ān fī al-Madrasah al-Thanawiyyah “Mu‘allimāt” Cukir Jombang - Kumala, Richa Nur; Muat (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2023)
Teaching grammar using the examples of Quranic verses is a subject taught in the high school by the teachers of cukir Jombang, and it is dedicated to the students program of memorizing the Quran. The objectives of this research are: 1) Knowledge of the application of grammar teaching using examples of Quranic verses in the seventh grade memorization of the Quran in the secondary school, cukir Jompang teachers, 2) Knowledge of the advantages and disadvantages of grammar teaching using examples of Quranic verses in the seventh grade memorization of the Quran in the secondary school, cukir Jompang teachers. This research is a descriptive qualitative study using three methods of data collection, namely observation, interviews and documentation. To answer the formulation of the existing problem, the researcher uses data analysis, data reduction, data presentation, data analysis and conclusions. The results of the research are as follows:1) The application of education in grammar using examples of Quranic verses has been implemented to the extent possible, which is generally going well and correctly according to the guidelines for the application of the method of education, which is the use of the standard method. Which begins by singing together and then explaining it and increasing practice. 2) The advantage of this method is that it shortens the delivery of materials and prioritizes practice at each meeting so that you can continue to control the abilities of the Pat. The disadvantages of teaching grammar using examples of Quranic verses in high school are parameters whose application is still relatively new, i.e. 3 years old, so there are still books towards needing to be reviewed or printed.